Direct and mediated associations among earnings quality, information asymmetry and the cost of equity - BHATTACHARYA, Nilabhra (Institutional Knowledge at Singapore Management University, 2012)
Using path analysis, we investigate the direct and indirect links between three measures of earnings quality and the cost of equity. Our investigation is motivated by analytical models that specify both a direct link and an indirect link that is mediated by information asymmetry, but do not suggest which link would be more important empirically. We measure information asymmetry as both the adverse selection component of the bid-ask spread and the probability of informed trading (PIN). For a large sample of Value Line firms during 1993–2005, we find statistically reliable evidence of both a direct path from earnings quality to the cost of equity, and an indirect path that is mediated by information asymmetry, with the weight of the evidence favoring the direct path as the more important.